(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2023)
This scientific article provides a large-scale study of trap seed machines in ginneries. Disadvantages of working machines in the plants are discussed, as well as selection varieties of cotton. In order to solve problems, experiments are given on the basis of selective varieties of seeds and the output of seeds on cotton-plated factories in areas